A novel and facile strategy to decorate Al2O3 as an effective support for Co-based catalyst in Fischer-Tropsch synthesis. (1st April 2021) - Guo, Shupeng; Niu, Congcong; Ma, Zhongyi; Wang, Jungang; Hou, Bo; Jia, Litao; Li, Debao
Graphical abstract: Highlights: Co catalysts supported on CN-decorated Al2 O3 were synthesized by a facile and green strategy. N could transmit electron to the cobalt surface and enhance the electron density of cobalt, then promoting the CO dissociation. N-doped catalysts show the high catalytic activity, C3 o/p and C5 + selectivity in FTS. Abstract: N-doped carbon materials have received much attention as an effective support to promote catalytic performance in FTS. However, complex and unfriendly preparation methods limit its wide application. Herein, we used a simple and harmless method to prepare CN-modified Co/Al2 O3 catalyst. It was found that the reducibility of catalyst was improved by the introduction of CN species and the electron density on cobalt surface was increased via the electron donation from the N dopants, especially for pyrrolic N, thus leading to the enhanced C5 + selectivity, C3 o/p ratio and TOF. Our work offers a new avenue to obtain high activity and selectivity catalyst.